"Napredni" proti "birokratskemu" socializmu - Krašovec, Primož (Šolsko polje, 2008)
This paper is a critical discourse analysis of the Yugoslav press coverage of Warsaw Pactćs occupation of Czechoslovakia in August 1968. We have analyzed the contents of 6 Yugoslav newspapers (two Slovenian, two Croatian and two Serbian). The article is divided into four parts. First part is an analysis ofthe distribution of newspaper space, typography and layout. Yugoslav newspapers have, once the occupation begun, changed their ordinary layout and space distribution to make place for intensive coverage of the occupation. This is how the event was made important on the level of newspaper form. Second part investigates the discursive construction of two opposing sets of values (one belonging to Yugoslav - humanist, democratic, progressive - version of socialism and the other to the opposing - authoritarian, bureaucratic - Soviet version of socialism). This was achieved by direct quotes and reprints of articles from the Soviet press, which were juxtaposed to Yugoslav interpretations and coverage of the event. Both sets of values established themselves as reaction to one another. In the third part we explained how this conflict of opposing sets of values represented a crisis ofsocialism, with occupation of Czechoslovakia being an example of both sets of values put into political action. In the last part we examined the discursive structure of this crisis of socialism and found out that it had a structure of Lacanian vel (ćyour money or your life!ć) - a forced alternative,which includes sacrificing one option to maintain the other. Two (Yugoslav and Soviet) versions of this alternative were inverse: in the Yugoslav version of the myth of socialism the correct choices in this vel werefreedom and democracy (the choice of the people of Czechoslovakia), while in the Soviet version the correct choice was to maintain the Stalinist socio-political order in Czechoslovakia. The right choice would, according to both versions, save socialism, while the wrong one would destroy it.
Keywords: 1968; Czechoslovakia; časopisi; Češkoslovaška; discourse; diskurz; education; ideologija; ideology; mit; myth; press; socialism; socializem; Šolsko polje; The School field; values; vrednote; vzgoja in izobraževanje